Theoretical Study on Thermoelectric Performance of N‐Type Mg3(Sb, Bi)2 Single Crystal for Cooling or Power Generation. Issue 7 (15th April 2022) - Li, Juan; Zhang, Shuai; Zheng, Shuqi; Han, Kai; Sun, Bing; Bi, Zuozhang; Wang, Xinle
Abstract: Mg3 Sb2 ‐based Zintl compounds have been paid much attention in recent years because of their high peak figure of merit ( zT ), however, there is room for the improvement of the average zT . In this work, the thermoelectric performance of Mg3 (Sb, Bi)2 single crystal by using density functional theory is investigated. The optimal carrier concentration ( n ) of Mg3 SbBi is 2 × 10 19 to 3 × 10 20 cm –3 at 100−700 K. At the n of 3 × 10 19 cm –3, it can exhibit a high average zT of ≈1.27 at cold‐side temperature ( T c ) of 300 K and hot‐side temperature ( T h ) of 700 K, and the electrical transport performance can be further improved by increasing the n . When the optimal n is reached, the maximum average zT of Mg3 SbBi at T c of 100 K and T h of 300 K can be up to 0.54, which is comparable to that of state‐of‐the‐art Bi2 (Te, Se)3 . Because the decreasing trend of the optimal n with temperature, the maximum low‐temperature thermoelectric performance is easier to be achieved by less extrinsic doping. This work reveals the great potential of Mg3 (Sb, Bi)2 single crystal for thermoelectric cooling or power generation, which is expected to provide useful guidance for thermoelectric devices. Abstract : This paper investigates the thermoelectric performance of Mg3 (Sb, Bi)2 single crystal in the temperature range of 100−700 K. The simulations predict the optimal carrier concentration, the maximum achievable electronic transport performance, and the average figure of merit of Mg3 SbBi single crystal. These results are expected to provide useful guidance for designing high‐performance thermoelectric materials for thermoelectric cooling or power generation.